Study on Multiplexing Channel Rental Rate Policy of Digital Television Operation in Indonesia - R Deiny Mardian Wijayapraja; Woro Indah Widiastuty; Tjandra Susila (Jetri : Jurnal Ilmiah Teknik Elektro, 2017)
Tariff regulation is essential to secure a competitive business. In digital television broadcasting, the multiplexing broadcast channel leasing tariff will greatly affect the competition between content or program service provider and multiplexing providers. Information about  competitions in digital television, especially in provision of digital television multiplexing infrastructure is needed. This research is conducted non only technically, but also from the point of view of regulation and business.  Regulatory analysis is carried out by referring to the implementation of existing regulation of digital television broadcasting in Indonesia and in other countries. In technical analysis, the technical calculations of deployment of the multiplexing infrastructure in service area is analized., The business analysis compared the ability of the purchasing power of the broadcasting content or program service provider with the  multiplexing channel leasing fare using various technical configurations. The tariff analysi focused on the possibility of appliying the upper and lower limit of the fare policies as well as the possibilities of the implementation of subsidized policies for the deployment of multiplexing infrastructure in a non economic areas. Keywords: digital television, regulation, tariff, broadcast, channel  ABSTRAK Regulasi tarif sangat penting dalam mengawal suatu bisnis yang kompetitif. Dalam bidang penyiaran televisi digital, tarif sewa saluran siaran multiplexing akan sangat berpengaruh terhadap kompetisi yang terjadi antara penyedia konten dan antar penyelenggara multiplexing sendiri. Informasi mengenai kompetisi di bidang televisi digital, terutama pada penyediaan infrastruktur multiplexing televisi digital sangat diperlukan. Untuk itu dalam penelitian ini dilakukan kajian baik secara regulasi, teknis dan bisnis. Analisis regulasi dilakukan dengan mengacu kepada regulasi  penyelenggaraan televisi digital yang sudah ada di Indonesia maupun di negara lain. Pada analisis teknis akan dibahas tentang perhitungan teknis penyelenggaraan infrastruktur multiplexing di wilayah pelayanan dan pada analisis bisnis akan dibandingkan kemampuan daya beli penyelengara konten terhadap tarif sewa saluran multiplexing dengan menggunakan berbagai konfigurasi teknis. Dalam analisis tarif, yang menjadi fokus adalah kemungkinan penerapan kebijakan tarif batas atas dan batas bawah, serta kemungkinan penerapan kebijakan subsidi untuk penyelenggaraan infrastruktur multiplexing di daerah nonekonomis.  Kata kunci: televisi digital, regulasi, tarif, penyiaran, saluran multiplexing